Structure and Strength of Bovine and Equine Amniotic Membrane - Wells HC; Sizeland KH; Kirby N; Haverkamp RG (MDPI (Basel, Switzerland), 2022)
Thin, strong scaffold materials are needed for surgical applications. New materials are required, particularly those readily available, such as from non-human sources. Bovine amniotic membrane (antepartum) and equine amniotic membrane (postpartum) were characterized with tear and tensile tests. The structural arrangement of the collagen fibrils was determined by small-angle X-ray scattering, scanning electron microscopy, and ultrasonic imaging. Bovine amnion had a thickness-normalized tear strength of 12.6 (3.8) N/mm, while equine amnion was 14.8 (5.3) N/mm. SAXS analysis of the collagen fibril arrangement yielded an orientation index of 0.587 (0.06) and 0.681 (0.05) for bovine and equine, respectively. This may indicate a relationship between more highly aligned collagen fibrils and greater strength, as seen in other materials. Amnion from bovine or equine sources are strong, thin, elastic materials, although weaker than other collagen tissue materials commonly used, that may find application in surgery as an alternative to material from human donors.
Keywords: SAXS; amnion; collagen; scaffold; 06 Biological Sciences